2011
DOI: 10.4061/2011/145626
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte Source and Hormonal Stimulation forIn VitroFertilization Using Sexed Spermatozoa in Cattle

Abstract: The aim of this study was to investigate the efficiency of in vitro embryo production in cattle utilizing sexed sperm from two bulls and oocytes recovered by OPU. Twenty donor animals were employed in eight OPU replicates: the first four OPU trials were conducted on animals without hormone treatment, and the last four were run on the same animals, following FSH subcutaneous and intramuscular administration. A higher rate of blastocyst development was recorded in stimulated, as compared to nonstimulated animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
1
12
2
1
Order By: Relevance
“…Reliable sorting of X-and Y-bearing sperm through flow cytometry impacts selection schemes and enable the cattle industries to enhance and accelerate the diffusion of production traits [2]. After the development of the sperm sorting industry, sexed sperm has been used for AI, in vitro fertilization (IVF) and intracytoplasmic sperm injection in several species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliable sorting of X-and Y-bearing sperm through flow cytometry impacts selection schemes and enable the cattle industries to enhance and accelerate the diffusion of production traits [2]. After the development of the sperm sorting industry, sexed sperm has been used for AI, in vitro fertilization (IVF) and intracytoplasmic sperm injection in several species.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro production (IVP) of embryos with sex-sorted sperm could justify the use of this sperm despite its higher price. Furthermore, we can increase the benefits of this technology by combining the use of sexed sperm in oocytes recovered by ovum pick-up [27] from donors previously superovulated, a treatment that improves the efficiency of the in vitro procedure compared with untreated donors [2].…”
Section: Introductionmentioning
confidence: 99%
“…Using OPU-derived oocytes, this finding has already been reported in buffalo (Liang et al, 2008) and in Bos indicus (Underwood et al, 2010). Pontes et al (2010), Senatore et al (2010) and Presicce et al (2010) showed the efficiency of in vitro embryo production in dairy taurus cattle utilizing sexed sperm and oocytes recovered by OPU, but the absence of control group (unsorted sperm) in all three experiments makes difficult to establish connections between the results of these studies and our data. Data with different superscripts (a, b) indicate values with significant differences (P< 0.05).…”
Section: Effect Of Sex-sorted Sperm On Embryo Developmentcontrasting
confidence: 51%
“…However, intrinsic differences were found between OPU oocytes and oocytes from slaughtered ovaries (Merton et al, 2003;Lopes et al, 2006;Presicce et al, 2010;Plourde et al, 2012). On the other hand, the quality of the in vitro-produced embryos from sex-sorted sperm may be affected due to the stress inherent to the sex-sorting process (Rath and Johnson, 2008); nevertheless, the results in this regard are not conclusive yet.…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation